2014
DOI: 10.1007/s13404-014-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Hardening effect of pre- and post-firing heat treatment for a firing-simulated Au-Pd-In metal-ceramic alloy

Abstract: The hardening effect of the pre-and post-firing heat treatments and their dual treatment was examined for a firingsimulated Au-Pd-In metal-ceramic alloy to determine if an additional post-firing heat treatment is effective in the hardening of an Au-Pd-In metal-ceramic alloy as well as to compare the hardening effects of pre-and post-firing heat treatments for a firing-simulated Au-Pd-In metal-ceramic alloy. The postfiring heat treatment was much more effective than the prefiring heat treatment or dual treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…2). Such rapid recovery in the hardness according to the cooling rate control during the porcelain firing process was also reported for Pd-Au-In-Ag and Pd-Ag-Au-Sn alloys, which had undergone a pre-softening heat treatment before porcelain firing 7,11) . From the above, if the readjustment is done for the ice-quenched metal substructure after degassing, it will increase the efficiency of processing without affecting the mechanical properties of the final prosthesis.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…2). Such rapid recovery in the hardness according to the cooling rate control during the porcelain firing process was also reported for Pd-Au-In-Ag and Pd-Ag-Au-Sn alloys, which had undergone a pre-softening heat treatment before porcelain firing 7,11) . From the above, if the readjustment is done for the ice-quenched metal substructure after degassing, it will increase the efficiency of processing without affecting the mechanical properties of the final prosthesis.…”
Section: Discussionsupporting
confidence: 62%
“…1), which is a relatively fast cooling rate. Such an effective cooling rate for alloy hardening was reported to vary according to the composition of the alloys 7,[10][11][12] . From the apparent hardening during cooling, the alloy was believed to have undergone precipitation or atomic ordering during cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the remainder of the firing process, the hardness decreased gradually, even though the peak intensity of the β precipitates increased further. FE-SEM, which showed the microstructural coarsening of the β precipitates through subsequent firing process, indicated that softening resulted from the release of lattice strain by the reduced interphase boundaries between the coarsened β precipitates and surrounding matrix [3,5].…”
Section: Resultsmentioning
confidence: 99%
“…Then during cooling to room temperature, the alloys can be hardened to some extent by atomic ordering or precipitation of the alloy components [1,2]. Therefore, depending on the composition, the alloy becomes much softer after several porcelain-firing cycles [3][4][5].…”
Section: Introductionmentioning
confidence: 99%